Pegcetacoplan for Geographic Atrophy Over 30 Months: Data From OAKS, DERBY, and the GALE Long-Term Extension Study - Goldberg, Roger A.; Boyer, David S.; Holz, Frank G.; MacCumber, Mathew W.; Garg, Sunir J.; Brown, David M.; Lad, Eleonora M.; Steinle, Nathan; Rishi, P. Singh; Pearce, Ian; Ach, Thomas; Ribeiro, Ramiro; et al. (Ophthalmic surgery, lasers & imaging, 2025)
Background and Objective This study will report safety and efficacy of pegcetacoplan for geographic atrophy (GA) secondary to age-related macular degeneration (AMD). Patients and Methods GALE is a phase 3, open-label, multicenter, 36-month extension of the OAKS and DERBY studies. Patients who received pegcetacoplan monthly (PM) or every other month (PEOM) in OAKS or DERBY continued the same regimen in GALE (PM-PM and PEOM-PEOM); sham-observed patients initiated pegcetacoplan, maintaining the same interval. Results In the first 6 months of GALE, 3.0% of study eyes developed exudative AMD, 1.3% intraocular inflammation, 0.1% ischemic optic neuropathy, and none endophthalmitis. Pegcetacoplan reduced GA growth rate by 39% (PM-PM) and 32% (PEOM-PEOM), with increasing efficacy over time across GA subtypes. In eyes with nonsubfoveal GA, pegcetacoplan reduced GA growth rate by 45% (PM-PM) and 33% (PEOM-PEOM). Conclusion Pegcetacoplan reduced GA growth rate up to 45% with increasing efficacy over 30 months and demonstrated a favorable safety profile. [Ophthalmic Surg Lasers Imaging Retina 2025;56:398–406.]